Loss of oligophrenin1 leads to uncontrolled Rho activation and increased thrombus formation in mice. (29th January 2015) - Fotinos, A.; Klier, M.; Gowert, N. S.; Münzer, P.; Klatt, C.; Beck, S.; Borst, O.; Billuart, P.; Schaller, M.; Lang, F.; Gawaz, M.; Elvers, M.
Summary Background Platelet cytoskeletal reorganization is essential for platelet adhesion and thrombus formation in hemostasis and thrombosis. The Rho GTPases RhoA, Rac1 and Cdc42 are the main players in cytoskeletal dynamics of platelets and induce filopodia and lamellipodia formation and actin polymerization to strongly increase the platelet surface upon activation. Moreover, they are important for platelet secretion, integrin activation and arterial thrombus formation. Objectives Rho GTPases are regulated by GTPase‐activating proteins (GAPs) that stimulate their GTPase activity to terminate Rho signaling. The regulation of Rho GTPase activity in platelets is not well defined. Recently, we identified oligophrenin1 (OPHN1), a RhoGAP in platelets that exhibits strong GTPase‐stimulating activity towards RhoA, Cdc42 and Rac1. Results In the present study we show for the first time, that deficiency of OPHN1 led to abnormal Rho activation and increased platelet cytoskeletal reorganization, including cell adhesion and lamellipodia formation on fibrinogen. Furthermore, platelets from ophn1−/− mice showed enhanced susceptibility to platelet activation with alterations in actin distribution and early release of granules. Platelet activation was enhanced following GPVI and PAR4 stimulation. This translated into elevated platelet thrombus formation and promoted arterial thrombosis under low shear conditions with altered hemostasis, as detected by tail bleeding time. Conclusions The results of the present study identified OPHN1 as an important regulator of platelet cytoskeletal reorganization and demonstrate that abnormal regulation of Rho proteins leads to increased platelet adhesion and thrombus formation under low shear conditions in vitro and in vivo, suggesting a prothrombotic phenotype of mice critical for acute thrombotic occlusions.